Undifferentiated carcinoma of the mesentery in a 51 year old male: A Case Report - Muhammad, Din; Alam, Jahangir; Islam, Sharmin (Journal of Shaheed Suhrawardy Medical College, 2017)
Undifferentiated carcinoma is a usually aggressive, malignant epithelial neoplasm composed of atypical cells which do not display evidence of glandular, squamous, or urothelial cell differentiation.1 Mesenteric tumors are rare and consist of a heterogeneous group of lesions. Among them undifferentiated carcinoma of the mesentery is very very rare entity. Here we present a case of undifferentiated carcinoma of the mesentery in a 51 year old male admitted to the department of surgery, Shaheed Suhrawardy Medical College Hospital (ShSMCH) with rapidly increasing huge abdominal lump, central abdominal pain and weight loss. Ultrasound of the whole abdomen and CT scan of whole abdomen reports were suggestive of retroperitoneal mass. Exploratory laparotomy was done and specimen sent for histopathology. Reports were suggestive of malignant mesothelioma whereas immunohistochemistry report revealed undifferentiated carcinoma of the mesentery. To the best of our knowledge, there was no report of undifferentiated carcinoma of the mesentery in a 51 year old male from Bangladesh or any other country J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 79-81